Beyond the bucket list: Unfinished and business among advanced cancer patients. Issue 11 (27th July 2018) - Masterson, Melissa P.; Slivjak, Elizabeth; Jankauskaite, Greta; Breitbart, William; Pessin, Hayley; Schofield, Elizabeth; Holland, Jason; Lichtenthal, Wendy G.
Abstract: Objective: The study aims to examine the prevalence and common themes of unfinished business (UB) and its associations with distress among advanced cancer patients. Methods: A total of 223 patients from a larger randomized controlled trial of Individual Meaning‐Centered Psychotherapy (IMCP) completed self‐report questionnaires that assessed UB and UB‐related distress, hopelessness, desire for hastened death, anxiety and depression, quality of life, spiritual well‐being, and purpose/meaning. Unfinished business themes were identified by qualitative analysis of open‐ended data. Results: A total of 161 (72%) patients reported the presence of UB. The mean UB‐related distress score was 7.01 (SD = 2.1) out of 10. Results of independent t tests showed that patients with UB reported significantly higher levels of anxiety and lower levels of existential transcendence than patients without UB. Linear regression equations indicated that UB‐related distress significantly predicted hopelessness ( F 1, 154  = 9.54, P  < 0.05, R 2  = 0.058), anxiety ( F 1, 154  = 4.31, P  < 0.05, R 2  = 0.027), personal meaning ( F 1, 136  = 6.18, P  < 0.05, R 2  = 0.043), and existential transcendence ( F 1, 119  = 6.7, P  < 0.05, R 2  = 0.053). Ten UB themes emerged from open‐ended responses; UB themes were not associated with UB‐related distress or psychological adjustment. Conclusions: Unfinished business was both prevalent and distressing in our sample. Findings underscore the need to develop and implement interventions designed to help patients resolve or find solace with UB.